Technical note - Assessment of nutrition data in West Africa - Transform Nutrition West Africa (International Food Policy Research Institute, 2019)
Transform Nutrition West Africa is a regional initiative to support effective policy and programmatic action on nutrition through evidence generation, synthesis and mobilization. This technical note provides methodological detail on the nutrition data assessment conducted for a set of 17 key nutrition indicators in the West African region. It includes the stepwise approach to map primary data sources and secondary data platforms and assess primary data sources across four quality measures for the nutrition indicators. Results are presented in individual country data profiles and spreadsheet, and can be visualized through an interactive online tool.